Neisseria Gonorrhoeae Spontaneous Bacterial Peritonitis - George Mwandia; Ryan Q. Simon; Hari Polenakovik; Katelyn J. Booher (Case Reports in Infectious Diseases)
We describe a case of gonococcal spontaneous bacterial peritonitis (SBP) in a 48-year-old sexually active female with alcoholic cirrhosis and chronic hepatitis B. She was admitted with fever, abdominal pain and distension without dysuria, dyspareunia, or vaginal discharge. On exam, she was icteric with features of sepsis and tense ascites. She underwent paracentesis. The ascitic fluid analysis revealed a neutrophil count of 1,050/µL, and culture grew Neisseria gonorrhoeae. Pelvic examination findings were negative for pelvic inflammatory disease; however, an endocervical swab was positive for N. gonorrhoeae by PCR. She was diagnosed with spontaneous bacterial peritonitis secondary to N. gonorrhoeae and was successfully treated with a seven-day course of IV ceftriaxone. N. gonorrhoeae spontaneous bacterial peritonitis is an extremely rare entity reported only twice despite the high prevalence of gonorrhoeae in the general population. We hypothesize that gonococcal SBP may be frequently undiagnosed since it responds to empiric antibiotics used to treat SBP. It is important for the clinician to be aware of gonococcus as a rare but potential pathogen in SBP. Future studies are needed to determine if routine gonococcal screening in SBP cases would be of clinical utility.